Barriers and facilitators in the management of preoperative thirst of the burned patient in the light of Knowledge Translation* - Garcia, Aline Korki Arrabal; Conchon, Marilia Ferrari; Pierotti, Isadora; Zampar, Elisangela Flauzino; Fonseca, Lígia Fahl (Revista da Escola de Enfermagem da USP, 2021)
Objective; To explore the perception of health care professionals about barriers and facilitators, and coping strategies for the implementation of the Thirst Management Model in the preoperative period of the burned patient. Method: This is a qualitative study, anchored in the conceptual framework Knowledge Translation. The focus group technique was chosen for data collection, composed by eight key professionals, to identify barriers and facilitators in evidence implementation and to point out coping strategies for the critical nodes found. Thematic Content Analysis technique was used to evaluate the data. Results: Five categories emerged: Physical structure, environment and supplies; Particularities of the burned patient; Human Resources; Team attitude; Team training and education. Coping strategies were raised for each barrier identified. Conclusion: The main barriers identified were found in the Human Resources and Team Attitude categories. The main facilitators were Particularities of the burned patient and Team training and education. The identification allowed planning coping strategies for critical nodes, providing support for scientific evidence in clinical practice.